THE EFFECT OF SUPPLY CHAIN MAPPING ON SERVICE DELIVERY IN MANUFACTURING INDUSTRIES. A CASE OF PICFARE INDUSTRIES LIMITED - ROGER MELLA MUTAI (Uganda Christian University, 2024)
This dissertation examines the effect of supply chain mapping on service delivery in manufacturing industries, with Picfare Industries Limited as a case study. The study assesses several key objectives: first, to assess the impact of supplier relationships on timeliness of service delivery at Picfare Industries Limited; second, to assess the impact of cost and timeframe establishment on customer satisfaction at Picfare Industries Limited; and third, to assess the impact of risk acknowledgement on accuracy of service delivery at Picfare Industries Limited. The study was carried out using a cross-sectional survey research design where quantitative research approach was used. A sample size of 67 was gotten using Taro Yamane’s formula although 60 of them responded to the study giving a response rate of 89.6%. The data was collected using questionnaires with staff of Picfare Industries Limited. The findings across the three objectives of my research at Picfare Industries Limited highlight significant factors impacting service delivery timeliness, customer satisfaction with cost and timeframe management, and the accuracy of service delivery impacted by risk acknowledgement. Risk acknowledgment and management, including strategies like local sourcing and supply chain resilience, play pivotal roles in enhancing service delivery accuracy by mitigating various risks such as natural disasters and economic shifts. Overall, these findings underscore the importance of proactive management practices and strategic partnerships in optimizing supply chain performance and customer satisfaction. Lastly, the study recommended Picfare to prioritize enhancing supplier relationships through collaboration, information sharing, and coordinated efforts to improve service delivery timeliness. Effective communication strategies should be emphasized to reduce lead times within the supply chain. Encouraging collaborative goals with suppliers can foster strong relationships and open communication channels, enhancing decision-making and problem solving, thereby positively impacting service delivery timeliness.